Preparation, model construction and efficacy lipid-lowering evaluation of kiwifruit juice fermented by probiotics. (June 2022) - Wang, Yu; Li, Hongcai; Ren, Yichen; Wang, Yaqin; Ren, Yaopeng; Wang, Xiaowei; Yue, Tianli; Wang, Zhouli; Gao, Zhenpeng
Abstract: In this study, kiwi juice was fermented with acid-resistant and bile-resistant probiotics to screen out lactic acid bacteria that can lower cholesterol and were suitable for kiwi fermentation. A non-linear fitting equation was used to establish a kinetic model of probiotics fermenting kiwi juice (R 2 > 0.90), and then a fermented juice with special effects of lowering fat was prepared. We have studied the lipid-lowering effect of fermented fruit juice through in vivo validation experiments in mice, and determined the lipid-lowering effect of fermented fruit juice according to the mouse serum indicators and the distribution of intestinal flora. The results suggested that the juice fermented with Bifidobacterium bifidum 6169 and Lactobacillus plantarum 21805 were more effective in cholesterol degradation, and the cholesterol degradation rates were 67.57% and 64.22%, respectively. The number of viable bacteria after fermentation was significantly higher than other groups ( p < 0.05), and the sensory score was also higher. In addition, the serum indicators were significantly ameliorated and the number of beneficial microorganisms in the intestinal flora increased after the high-fat mice were treated with fermented kiwifruit juice. The research indicates that the fermented products have a regulatory effect on cholesterol levels in mice with hyperlipidemia. Highlights: Bifidobacterium bifidum and Lactobacillus plantarum had strong cholesterol degradation rate in vitro . The kinetic model of kiwi juice fermentation by probiotic mixed bacteria was constructed. Kiwifruit juice fermented by probiotics can improve dyslipidemia, liver disease and intestinal flora. The result obtained will provide a reference for fruit deep processing.